Being recognised as a whole person: A qualitative study of inpatient experience in mental health. (1st February 2019) - Eldal, Kari; Natvik, Eli; Veseth, Marius; Davidson, Larry; Skjølberg, Åse; Gytri, Dorte; Moltu, Christian
Abstract: Few studies address the many challenges that are faced by staff and patients in the inpatient mental health context. In particular, there is a lack of research that explores first-hand patient experiences in order to establish what treatment practices best assist patient recovery and what are the barriers to these practices. This qualitative study, which utilises a user-involved research framework, collaborates with a co-researcher patient group throughout the study. Fourteen patients, all of whom had been in inpatient treatment for at least three weeks, were recruited to the study. Study participants were interviewed in-depth in the period September 2016 to March 2017. Data underwent a thematic analysis that was inspired by interpretative phenomenological analysis. A core theme of the findings was the importance of being recognised as a whole person, and the patient–professional relationship was regarded as a fundamental factor in fostering recovery, with two underlying themes: (i) a need to have one's self-identity recognised and supported, and (ii) an experience of ambivalence between needing closeness and distance. This study suggests ways nurses can give priority to interpersonal interactions and relationships with hospitalised patients over task-oriented duties, highlighting the need for nurses to balance patient competing needs for both closeness and distance.